2007
DOI: 10.1017/s0266467407004051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sowing, canopy cover and litter on seedling dynamics of two Polylepis species at upper tree lines in central Ecuador

Abstract: Failure of reproduction is hypothesized as being a main reason for the formation of upper tree lines but there is, as yet, little supportive evidence of such. This study investigates the effects of experimental sowing, canopy cover and litter depth on seedling emergence and survival of Polylepis incana and Polylepis pauta at the upper distribution limit of the species in the Páramo de Papallacta, central Ecuador. We established 18 study plots located in the interior, at the edge and at the exterior of closed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 35 publications
(46 reference statements)
2
24
0
9
Order By: Relevance
“…The absence of such structure in populations of mature individuals is consistent with theoretical predictions for tree populations which are characterized by generally low genetic structure (Hamrick andGodt 1989, 1996;Nybom 2004). High seedling mortality (observed in Polylepis incana, P. pauta, [Cierjacks et al 2007], and P. australis [Enrico et al 2004]) and delayed reproductive maturity in trees could contribute to the attenuation of structure over time (Austerlitz et al 2000;Le Corre and Kramer 2003). No correlation was found between geographic distance and genetic differentiation, and clustering of populations on the basis of genetic affinity often revealed higher genetic similarity between populations in different basins, which may have been caused by greater gene exchange between river basins.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of such structure in populations of mature individuals is consistent with theoretical predictions for tree populations which are characterized by generally low genetic structure (Hamrick andGodt 1989, 1996;Nybom 2004). High seedling mortality (observed in Polylepis incana, P. pauta, [Cierjacks et al 2007], and P. australis [Enrico et al 2004]) and delayed reproductive maturity in trees could contribute to the attenuation of structure over time (Austerlitz et al 2000;Le Corre and Kramer 2003). No correlation was found between geographic distance and genetic differentiation, and clustering of populations on the basis of genetic affinity often revealed higher genetic similarity between populations in different basins, which may have been caused by greater gene exchange between river basins.…”
Section: Discussionmentioning
confidence: 99%
“…This was attributed to differences in seed rain, but also to constraints in seedling survival under open conditions. Seeding experiments on Polylepis forests at the treeline in Ecuador showed that microclimatic conditions hamper seedling emergence in open grassland at the treeline compared to the forest edge or its interior (Cierjacks et al 2007). This was related to the special microclimatic conditions near the soil surface: like in our study, mean air and soil temperatures near the ground were slightly cooler inside the uppermost forest, while air temperature in the grassland outside the treeline forest showed markedly higher maximum and lower minimum temperatures compared to the forest conditions.…”
Section: Regeneration Under Different Microclimate Conditionsmentioning
confidence: 99%
“…Sowing experiments performed inside exclosures demonstrated that seedling emergence of both Polylepis species was < 1% of the sown seeds (Cierjacks et al 2007a). This is clearly lower than the 2-6% germination rate under controlled conditions in the laboratory (A. Cierjacks, unpublished data, see also Brandbyge and Holm-Nielsen 1992).…”
Section: A Comparison Of the Regeneration Of Erica Spp In East Africmentioning
confidence: 99%